Self-citation in countries: comparisons between the global south and north using the OpenAlex Database - Sandro Barbosa de Oliveira; João de Melo Maricato (Em Questão)
This paper aims to examine self-citation rates in developed and developing countries, as well as across the Global North and South, and explore their relationship with scientific productivity. Methods: The study utilized data from the OpenAlex database, encompassing 12.3 million articles from 50 countries published between 2020 and 2023. Self-citation rates were calculated at the country and socioeconomic region levels, based on the proportion of articles citing works originating from the same country. Results: Developing countries exhibited higher adjusted self-citation rates and stronger correlations between scientific output and self-citation. In contrast, developed countries showed weaker correlations between productivity and citations, with their citations being less focused on domestic works. While Global South countries account for 42.6% of total scientific output, their contributions represent only 10.4% of references in publications from developed countries, reflecting a concentration of citations among Global North nations. Conclusion: Despite the increasing contribution of developing countries to global scientific output and their growing representation in the OpenAlex database, these countries display high self-citation rates. Moreover, citations from developed countries remain largely concentrated within their own group, underscoring persistent inequalities in the flow of knowledge between the Global North and South.